The Pengaruh Penambahan Sekam Padi Pada Pembuatan Pelet Biomassa Eceng Gondok Menggunakan Metode TOSS: Pengaruh Penambahan Sekam Padi Pada Pembuatan Pelet Biomassa Eceng Gondok Menggunakan Metode TOSS - Fadjar Goembira; Yommi Dewilda; Zalwa Andini Putri; Arief Noerhidayat (Dampak, 2025)
ABSTRACT The Teknologi Olah Sampah di Sumbernya (TOSS) method can be an alternative to reduce biomass waste such as water hyacinth. The TOSS method converts water hyacinth waste into biomass pellets through three stages: shredding process, biodrying process, and pelletization process. Water hyacinth waste has a low calorific value so it is necessary to add other materials with higher calorific values such as rice husks. This research was conducted using TOSS method, incorporating AR124 bioactivator in biodrying process and the addition of rice husk during the pelletization process. This research aims to analyze and evaluate the biodrying process of water hyacinth waste using AR124 bioactivator through measurements of moisture content, temperature, shrinkage, odor, and duration of the biodrying process. In addition, the study also analyzed and evaluated the quality of water hyacinth biomass pellets without and with the addition of rice husk based on proximate analysis and calorific value according to the quality standards of SNI 8966: 2021 about Refused Derived Fuel (RDF) for Power Plants. The 10-day biodrying process showed a moisture content of 20.1%, pH 7.0, shrinkage of 3 cm, highest temperature of 29°C on the first day, and no odor since day 5. Variations in the ratio between water hyacinth and rice husk, namely D (1:0), A1 (1:1), A2 (1:2), and A3 (1:3), were tested in triplicate. The results showed that all variations met the quality standards in accordance with SNI 8966:2021. A3 was the best variation with a moisture content of 3.11%, ash content of 17.83%, fixed carbon of 16.68%, volatile substances of 62.39%, and calorific value of 16.92 MJ/kg (4,041 kcal/kg). The addition of rice husk is proven to increase the calorific value of biomass pellets from standard class 3 to class 2 according to SNI 8966:2021. Keyword: bioactivator AR124, biomass pellets, rice husks, teknologi olah sampah di sumbernya (TOSS), water hyacinth